Judicial Judgments, Do They Violate the Regulatory Principles? - Barreda Tamayo, Carlos (2015)
In November 2014 the Fourth Court for Administrative Matters ruled that OSINERGMIN give effect to Resolution of Disputes Transitional Administrative Chamber of the Superior Court of Lima, which established the dealership ENERSUR Electricity generation has no responsibility for payment the use of a secondary power transmission system Chilca - Independencia, contrary to Law 28832 which ensures the efficient development of electricity generation.The Judiciary based its decision on an incorrect interpretation of the concession contract Electricity Transmission Red de Energía del Peru (REP) with the State to apply to ENERSUR. The decision of the judiciary is illegal, creates anti-technical precedent, violating the regulatory principles of independence, neutrality, competition, non-discrimination and harms millions of users to increase electricity tariffs for compliance.